Modal Sosial Sebagai Bentuk Manajemen Konflik pada Komunitas Nelayan di Kabupaten Aceh Barat - Rahmat Dilta Harahap (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
The fisheries industry is a crucial agricultural sector that significantly impacts regional development. It encompasses all activities involving the management of fish resource utilization and their surroundings. Desa Kuala Bubon is part of a community that can access abundant coastal resources in Aceh Barat Regency, with most of the population working as fishermen. The research aims to describe conflict and the social capital part applied to conflict management in fishing communities. This research was conducted in October-December 2023. In this investigation, there were eight essential informants. This research uses qualitative methods with qualitative descriptive research. The data analysis uses qualitative analysis of the Miles and Huberman model. The results show that there are still conflicts in managing coastal resources in the Fishermen’s Community. Five main types of conflict were identified. These conflicts are caused by different perceptions and interests among fishermen that affect their social lives. This research also shows the importance of social capital, which includes trust, social norms, and social participation, in overcoming conflicts. The social capital component can be an alternative to conflict management in the fishing community of Desa Kuala, which can be done by strengthening social capital, namely increasing trust between parties, establishing and implementing binding social norms, and building active social participation. Social capital consisting of shared values and norms can help establish cooperation and improve the quality of relationships between fishermen. Fair implementation of rules and strict supervision by authorities are also essential to reduce conflict and ensure sustainable resource use.